Development of a science, environment, technology, and society-based learning module to foster critical thinking in elementary students - Yulianti, Dwi; Herpratiwi, Herpratiwi (Journal of Education and Learning (EduLearn), 2024)
This study aims to develop a science, environment, technology, and society (SETS)-based learning module to enhance critical thinking skills among elementary school students. Employing a research and development (RD) approach adapting the Borg and Gall model, this module is designed to enrich the learning process of natural and social sciences (IPAS). The research sample involved elementary school students from selected schools, utilizing quantitative methods to measure the module's effectiveness. Validation results showed high scores in content, media, language, and pedagogy, indicating a highly valid module. Practicality tests revealed high practicality from both learners' and educators' perspectives, with average scores above 90. The findings indicate a significant increase in students' critical thinking abilities post-module learning, as measured by pre-test and post-test instruments. Implications of these findings suggest that integrating SETS concepts into IPAS learning can be an effective strategy in enhancing elementary students' critical thinking skills. These findings also offer insights for educational practitioners in designing more interactive and environmentally relevant learning materials.